The mediator role of online gaming time and dysfunctional belief in the relationship between level of internet gaming addiction and perceived social support in adolescents - Yavuz, Oğuzhan; Erden Çınar, Seval (Journal of Dependence, 2022)
Objective: The aim of this research was to examine as the direct, indirect and total effects of perceived social support, dysfunctional belief and weekly hours of online gaming time on internet gaming addiction. Method: Correlational research design was used in the study. The participants of the research consist of 300 volunteer adolescents, 190 males and 110 females, aged 15-17, studying at high schools in Ümraniye district of Istanbul. The sample of the study was selected by convenient sampling method. In the study, “Internet Gaming Disorder Scale-Short Form”, “ Social Support Appraisals Scale To Be Used With Children And Adolescents”, “Online Cognitions Scale” were used. Results: The mediating role of dysfunctional belief was found between perceived social support and internet gaming addiction(bootstrap = -.160, 95% CI = -.261, -.078). The mediating role of weekly hours of online gaming time was found between perceived social support and internet gaming addiction (bootstrap = -.160, %95 GA = -.261, -.078). Finally, it was found that weekly hours of online gaming time and dysfunctional beliefs had a sequential mediating role in the relationship between perceived social support and internet gaming addiction (bootstrap =-.107, 95% CI =-.173,-.062). Conclusion: The decrease in the level of perceived social support increases the weekly hours of online gaming time, along with the increase in dysfunctional beliefs, and therefore these interactions increase the game addiction on the internet.